Treatment satisfaction in people with type 2 diabetes mellitus treated with once‐weekly dulaglutide: data from the AWARD‐1 and AWARD‐3 clinical trials. Issue 9 (27th July 2015) - Reaney, M.; Yu, M.; Lakshmanan, M.; Pechtner, V.; van Brunt, K.
<x xml:space="preserve">Abstract</x> Aims To compare treatment satisfaction among people with type 2 diabetes receiving dulaglutide 1.5 mg and dulaglutide 0.75 mg (a once‐weekly, long‐acting, glucagon‐like peptide‐1 receptor agonist) with those receiving either exenatide or placebo (AWARD‐1 study) or metformin (AWARD‐3 study) over 52 weeks. Methods The Diabetes Treatment Satisfaction Questionnaire status version (DTSQs) and change version (DTSQc) were used to evaluate total treatment satisfaction and perceived frequency of hyperglycaemia and hypoglycaemia. Results In the AWARD‐1 study, significant improvements from baseline were observed in total DTSQs score for both dulaglutide doses (26 and 52 weeks) and exenatide (26 weeks). The improvement was significantly greater with both dulaglutide doses compared with placebo (26 weeks) and exenatide (26 and 52 weeks). The perceived frequency of hyperglycaemia was lower for all groups at 26 and 52 weeks compared with baseline. The improvement was greater with both dulaglutide doses and exenatide compared with placebo at 26 weeks, and was also greater with both dulaglutide doses compared with exenatide at 26 and 52 weeks. The exenatide group had an increase in perceived frequency of hypoglycaemia at 26 and 52 weeks. In the AWARD‐3 study, significant improvements from baseline were observed for total DTSQs scores in all groups at 26 and 52 weeks. Perceived frequency of hyperglycaemia was lower for all groups at 26 and 52 weeks compared with baseline, and this improvement was greater with both dulaglutide doses compared with metformin at 52 weeks. Conclusions Dulaglutide was associated with improvements in treatment satisfaction and a decrease in perceived frequency of hyperglycaemia.